Enterprise, Inequality and Economic Development - Dan Bernhardt; Huw Lloyd-Ellis (Queen's University, Department of Economics, 1993)
We develop a dynamic general equilibrium model of economics development with altruism in which the evolution of the extent of entrepreneurship, the rate of rural-urban migration, the scale and structure of production and the degree of income and wealth inequality are endogenously determined. The model generates a development process that has distributional characteristics consistent with those of the Kuznets hypothesis. In early stages of development agents face binding financing constraints so that production is only carried out on a small scale. Few agents earn entrepreneurial profits and the lack of competition for labor keeps the wage low. The scale of production gradually expands as the descendants of entrepreneurs face less stringent financing constraints. Income and wealth inequality become increasingly acute as the entrepreneurial rich get richer and the poor remain so. Eventually, competition for workers drives up wages. As the labor share of income rises, the quality of entrepreneurs improves and the scale of production and the profits of an entrepreneur, controlling for wealth and ability, fall. Consequently, as the development process continues, income and wealth disparities eventually decline. With no engine for technological advancement, the economy converges to an invariant, non-degenerate wealth and income distribution. The economy may even be asymptotically efficient, as the "right" entrepreneurs take on investment projects. We derive the time path of the optimal redistribution policy and detail the impact of aggregate shocks at different stages. Finally, we provide insight into why the "Kuznets curve" may appear in some economies but not in others, and how long-run fluctuations in economic activity can arise endogenously.
Keywords: E0; O1; O4; 330; size-distribution; heterogeneity; altruism; wealth constraints